SINTESIS DAN KARAKTERISASI β-TRICALCIUM PHOSPHATE BERBASIS CANGKANG KERANG RANGA PADA VARIASI SUHU SINTERING - N. Selvia (Jurnal Biofisika, 2012)
Many  cases  of  bone  loss  triggered  growing  research  of  bone  biomaterial. Biomaterials are widely used for bone substitution is β-tricalcium phosphate (β-TCP). In this research was done the synthesis of β-TCP based on rangga shells. The use of natural materials (shells) can improve the bioactive properties and biocompatibility in the  process  of  bone  healing.  Rangga  shells  obtained  from  the  Riau  Islands. Synthesis of β-TCP performed by reacting calcium from rangga shell and H3PO4 with precipitation method at a temperature of 80oC with variations sintering temperature to 800oC,  900oC,  1000oC,  1100oC,  1200oC,  and  1300oC.  To  determine  the  phase formed in the samples analyzed using X-ray difraction (XRD). XRD pattern shows the presence of peaks belongs  to β-TCP, hydroxyapatite (HA), carbonate apatite tipe-A (CAA),  and  oktacalcium  phosphate  (OCP).  β-TCP  optimum  form  on  the  β-TCP samples sintering temperature 1200oC holding time 7 hours with the percentage of β-TCP  produces  by  81,98%.  The  formation  of  β-TCP  was  also  stregthened  by  the results of  Fourier  transform infrared characterization (FTIR) is characterized by the presence of phosphate (PO43-) and hydroxyl (OH-). Micrograph of scanning electron microscopy  (SEM)  on  sample  of  β-TCP  optimum  β-TCP  showed  in  the  form  of chunks that are composed into a coarse aggregate. β-TCP  optimum sample has an average particle size of 693,65 nm were measured using the PSA.